The role of in-situ nano-TiB2 particles in improving the printability of noncastable 2024Al alloy. Issue 10 (3rd October 2022) - Sun, Tengteng; Wang, Hongze; Gao, Zhenyang; Wu, Yi; Wang, Mingliang; Jin, Xinyuan; Alex Leung, Chu Lun; Lee, P.D.; Fu, Yanan; Wang, Haowei
Abstract : In-situ pre-decorated different content of TiB2 particle reinforced 2024 Al matrix composites ( x TiB2 /2024Al composite, x = 0, 1, 2, 4, 6, 8 wt.%) were printed by laser powder bed fusion (LPBF). A quantitative equation was established to quantify heterogeneous nucleating potency by TiB2 nanoparticles on the grain size of the LPBFed samples. Optimized mechanical properties were obtained in the as-printed 4TiB2 /2024Al alloy which proved the feasibility of replacing the wrought part with the LPBFed one. This manuscript provides a method to determine the optimized content of TiB2 nanoparticles to change the noncastable material to the printable one. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: This manuscript provides a method to determine the optimized TiB2 content to change the noncastable material to the printable one, and can potentially guide the introduction of many other nanoparticles.